Nonsurgical management of odontogenic maxillary sinusitis – Two case reports - André Luiz da Costa Michelotto; Lisa Yurie Oda; Wagner Hummig; Antonio Batista (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial, 2025)
Odontogenic maxillary sinusitis is a sinus pathology secondary to maxillary dental pathologies or complications from dental procedures. Due to its clinical presentations of sinonasal symptoms, odontogenic sources may be underdiagnosed, leading to an incorrect treatment. This report presents two cases in which odontogenic maxillary sinusitis was correctly diagnosed and treated by nonsurgical endodontic management. In both cases, the patients presented with pain or discomfort in the maxillary region, and the cone-beam computed tomography revealed thickening of the maxillary sinus membrane, which was helpful for the diagnosis and follow-up. In the first case, the tooth related to the pathology underwent primary nonsurgical endodontic treatment, while in the second case, the tooth underwent nonsurgical endodontic retreatment. In both cases, calcium hydroxide dressing was used between appointments, and the root canals were filled with gutta-percha cones and bioceramic sealer. The follow-up cone-beam computed tomography obtained 24 months later in the first case and 16 months in the second showed the absence of maxillary sinus abnormalities, and the patients presented without clinical symptoms. The clinician must be aware of the signs and symptoms related to odontogenic maxillary sinusitis to be successful in diagnosis, planning, and treatment.